Altered Effective Connectivity of the Primary Motor Cortex in Transient Ischemic Attack. (18th November 2022) - Hao, Zeqi; Song, Yulin; Shi, Yuyu; Xi, Hongyu; Zhang, Hongqiang; Zhao, Mengqi; Yu, Jiahao; Huang, Lina; Li, Huayun
Abstract : Objective . This study is aimed at exploring alteration in motor-related effective connectivity in individuals with transient ischemic attack (TIA). Methods . A total of 48 individuals with TIA and 41 age-matched and sex-matched healthy controls (HCs) were recruited for this study. The participants were scanned using MRI, and their clinical characteristics were collected. To investigate motor-related effective connectivity differences between individuals with TIA and HCs, the bilateral primary motor cortex (M1) was used as the regions of interest (ROIs) to perform a whole-brain Granger causality analysis (GCA). Furthermore, partial correlation was used to evaluate the relationship between GCA values and the clinical characteristics of individuals with TIA. Results . Compared with HCs, individuals with TIA demonstrated alterations in the effective connectivity between M1 and widely distributed brain regions involved in motor, visual, auditory, and sensory integration. In addition, GCA values were significantly correlated with high- and low-density lipoprotein cholesterols in individuals with TIA. Conclusion . This study provides important evidence for the alteration of motor-related effective connectivity in TIA, which reflects the abnormal information flow between different brain regions. This could help further elucidate the pathological mechanisms of motor impairment in individuals with TIA and provide a new perspective for future early diagnosis and intervention for TIA.